PAI Digital Mosaic: Learning Creation Through Software-Based Media - Ratna Putri Pradita; Qo-Idah Ariq Pangesti; Anugrah Ainul Yakin; Muh. Alif Kurniawan (Penerbit Hellow Pustaka, 2024)
In the increasingly developing digital era, Islamic Religious Education (PAI) learning faces new challenges and opportunities. This article introduces the concept of